PROMOTION OF HUMANISM IDEAS IN PIRIMKUL KADYROV’S WORK (TAMADDUN NURI JURNALI, 2025)
This research paper deals with humanitarian qualities in the works of Pirimkul Kadyrov. The topic will be covered by the example of the author`s works.